2016
DOI: 10.1186/s12963-016-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the prevalence of thyroid disorders in the adult population of Northeast Germany

Abstract: BackgroundOnly a few studies like ours have investigated the effect of long-term stable iodine supply on thyroid disorders in a historically iodine-deficient population, but not with a long follow-up time of 10 years.MethodsData were derived from two independent population-based cohorts of the Study of Health in Pomerania (SHIP-0 [1997–2001] and SHIP-TREND [2008–2012]) comprising 4308 and 4420 subjects, respectively. Diagnosed thyroid disorders were assessed. Thyroid gland dimensions were examined by ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 44 publications
2
34
1
3
Order By: Relevance
“…However, other studies report no increase or a reduction in thyroid autoimmunity with time following fortification . The analysis of epidemiological data from a mildly iodine‐deficient population in Tasmania found no association between iodine supplementation and an increase of thyroid autoimmunity between 1995 and 2013 …”
Section: Thyroid Disorders Associated With Iodine Excessmentioning
confidence: 96%
See 1 more Smart Citation
“…However, other studies report no increase or a reduction in thyroid autoimmunity with time following fortification . The analysis of epidemiological data from a mildly iodine‐deficient population in Tasmania found no association between iodine supplementation and an increase of thyroid autoimmunity between 1995 and 2013 …”
Section: Thyroid Disorders Associated With Iodine Excessmentioning
confidence: 96%
“…However, other studies report no increase or a reduction in thyroid autoimmunity with time following fortification. 113,154,[156][157][158] The analysis of epidemiological data from a mildly iodinedeficient population in Tasmania found no association between iodine supplementation and an increase of thyroid autoimmunity between 1995 and 2013. 158 Improved diagnostic criteria and increasing the use of screening technologies for the thyroid (particularly thyroid ultrasound) have led to increased detection of mild thyroid disorders; this has likely contributed to an increase in the incidence of thyroid disorders and biased comparison over time.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Undiagnosed thyroid disorders (morphological or functional) are found in up to 75% of the population [4,5]. Thyroid nodules are detected in 30 to 68% [4,6,7], most of them as incidental findings [2,8,9]. Some studies observed an increasing prevalence of thyroid nodules, most likely due to an improved resolution of thyroid ultrasound devices, which are now able to detect thyroid nodules of 2 to 3 mm [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules are detected in 30 to 68% [4,6,7], most of them as incidental findings [2,8,9]. Some studies observed an increasing prevalence of thyroid nodules, most likely due to an improved resolution of thyroid ultrasound devices, which are now able to detect thyroid nodules of 2 to 3 mm [2,6,7]. The Study of Health In Pomerania (SHIP) found elevated serum thyroid-stimulating hormone (TSH) levels in 4% and the Kooperative Gesundheitsforschung in der Region Augsburg (KORA) in 14% of study participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation